Pengaruh Disiplin Kerja dan Pengalaman Kerja terhadap Produktivitas Kerja Karyawan PT. Grand Twins Engineering - Satim Hamid; Jon Edy; Muhammad Maulana; Imam Mahdi Idzul Tsani (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to analyze the effect of work discipline and work experience on employee productivity at PT. Grand Twins Engineering. The research background is based on productivity fluctuations during 2022–2024, where production realization never met the target and significantly declined in 2024. This condition indicates fundamental problems in work behavior and human resource management. Work discipline, including compliance with rules, attendance consistency, and responsibility, is considered an important factor in increasing productivity. Meanwhile, work experience, reflected in years of service, technical skills, and practical knowledge, is believed to enhance employee effectiveness. This study applied a quantitative approach with an associative research type. The population consisted of 120 employees, with 92 respondents selected using Slovin’s formula. Data were collected through questionnaires, interviews, company documents, and relevant literature. The research instrument had been tested for validity and reliability, with all items meeting the requirements. The results of multiple linear regression analysis showed that work discipline had a significant positive effect on productivity (t-count 3.117 > t-table 1.986). Work experience also had a significant effect (t-count 5.119). Simultaneously, both variables significantly influenced productivity (F-count 43.483 > F-table 3.10). The determination coefficient (R²) of 0.494 indicated that 49.4% of productivity variation was explained by discipline and experience, while the remaining 50.6% was influenced by other factors such as motivation, leadership style, and compensation.